PENGUATAN KEWENANGAN LEMBAGA BADAN PENGAWAS PEMILU DALAM PENEGAKAN HUKUM PEMILU - Angelo Emanuel Flavio Seac (Legal Spirit, 2017)
This study is based on the high administrative and criminal violations in the elections in Indonesia, so an assessment is needed to strengthen the authority of Bawaslu in the implementation of elections, in order to improve the quality of elections, and create good electoral law enforcement practices in Indonesia. To study this matter, hence in this research a normative juridical research, using approach statute approach, historical, conseptual, case, and comparative approaches was employed. Then the collected legal materials were descriptively and qualitatively analyzed. The strengthening of this delicate authority is accomplished by accompanying improvement in some other vital aspects such as the regulatory improvements on the institutional and electoral arrangements that give Bawaslu a more assertiveness space that is more ideal in the electoral law enforcement. Keywords: Bawaslu, Strengthening Authority, Law Enforcement, Election